Grow the Plant!: An Environmental-Themed Board Game as A Sustainable Living Learning Medium for Elementary School Students - Nisa, Fika Khoirun; Fahminnansih, Fenty; Erdiana, Setya Putri (FKIP Universitas Lampung, 2023)
Grow the Plant!: An Environmental-Themed Board Game as A Sustainable Living Learning Medium for Elementary School Students. Objectives: This research aims to enhance awareness and understanding of sustainability issues through an enjoyable educational game at the UNESA Laboratory Elementary School. Methods: This research employs the Design Thinking method with qualitative data analysis. There were 20 participants aged 8-12 years who participated in answering the research questionnaire. Data is presented and described based on the percentages obtained from the questionnaire results. Findings: This research indicates that 90% of the users of the